Sportklubok és városi fejlődés: Szinergiák Magyarországon - Faragó, Beatrix (Közép-Európai Közlemények, 2025)
Sports clubs play a significant role in urban development in Hungary, both economically and socially. These institutions not only shape the local sports scene but also function as community centres that contribute to improving the health of the population and strengthening community cohesion. Events, competitions, and trainings organized by sports clubs stimulate the development of urban infrastructure, especially in terms of sports facilities, transport networks and services. The purpose of the study is to show what concrete synergies these institutions create with local economies and social processes, as well as how they contribute to the sustainable development of cities. The analyses focus on sports organizations in Hungary, regarding the number of sports clubs, their revenues and employment indicators.